Teaching social communication to children with autism : a practitioner's guide to parent training [elecrtonic resource] - 516335 Ingersoll, Brooke; Ingersoll, Brooke; Dvortcsak, Anna (New York : The Guilford Press, 2010)
Includes bibliographical references and index